What's for dinner, thankyou! - Hopkins, Ted, 1949-; Hude, Felix; Oehme, Angelika; Gerrard, Graeme; Bencina, Ross. (Rowville, Vic. : Dataworks, 1995)
Introduces the user to the unique world of the Antarctic. Shows how the extraordinary creatures that live there can manage to eat and survive.
System requirements, Windows: any PC which complys to MPCII standard; Windows 3.1; 8 or 16 bit stereo sound 4Mb RAM; video display supporting a resoulution of 640x480 in 256 colors and a double speed CD-ROM drive.
System requirements, Macintosh: Macintosh Computer with 4Mb of RAM, a video display supporting a resolution of 640x480 with 256 colors, a double speed CD-ROM drive and System 6.0.5 or later.
Title from disc label.
Animations by Felix Hude; voice, environmental sounds and original compositions by Ross Bencina and Graem Gerrard; text by Ted Hopkins and Angelika Oehme.
Keywords: Animals -- Food -- Juvenile software; Antarctica -- Juvenile software